2019
DOI: 10.1002/mren.201800065
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of Styrene and Cardanol from Cashew Nut Shell Liquid. Part I – Kinetic Modeling of Bulk Copolymerizations

Abstract: The present manuscript investigates the bulk copolymerization of styrene and cardanol from cashew nut shell liquid. A kinetic mechanism is proposed and a mathematical model is derived. The model parameters are estimated in order to allow for appropriate description of monomer conversions, average molecular weights, and copolymer compositions of the produced copolymer. It is shown that cardanol exerts strong inhibitory effects on styrene polymerization, making incorporation of cardanol into the copolymer chains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The internal (and less reactive) double bonds of cardanol chains probably captured the free radical needed to initiate the polymerization, inhibiting the reaction. 31 Figure 1b illustrates the reaction kinetics of polymerizations based on MMA copolymers. It can be observed that the addition of DVB also caused a significant increase in the reaction rate and that cardanol inhibited the polymerization reaction once more.…”
Section: Resultsmentioning
confidence: 99%
“…The internal (and less reactive) double bonds of cardanol chains probably captured the free radical needed to initiate the polymerization, inhibiting the reaction. 31 Figure 1b illustrates the reaction kinetics of polymerizations based on MMA copolymers. It can be observed that the addition of DVB also caused a significant increase in the reaction rate and that cardanol inhibited the polymerization reaction once more.…”
Section: Resultsmentioning
confidence: 99%
“…15 Unmodified cardanol was directly used as a comonomer in the radical suspension polymerization of methyl methacrylate or styrene, however the poor reactivity of the alkyl chain unsaturations limited its incorporation in the final copolymer. 16,17 Linear poly(cardanol) was also obtained from unmodified cardanol using a Friedel-Crafts alkylation polymerization mechanism. 18 Cardanyl acrylate was polymerized in solution using free radical polymerization [19][20][21] or controlled ATRP.…”
Section: Introductionmentioning
confidence: 99%
“…Polymers with favorable mechanical properties were prepared by reacting allyl‐containing cardanol derivatives with bismaleimide compounds by addition copolymerization 15 . Unmodified cardanol was directly used as a comonomer in the radical suspension polymerization of methyl methacrylate or styrene, however the poor reactivity of the alkyl chain unsaturations limited its incorporation in the final copolymer 16,17 . Linear poly(cardanol) was also obtained from unmodified cardanol using a Friedel‐Crafts alkylation polymerization mechanism 18 .…”
Section: Introductionmentioning
confidence: 99%